Rewriting and Redefining the Aspects of Marketing with Metaverse – A Brief Insight - Biswas, Wendrila (Indian Journal of Marketing, 2023)
Purpose : With the emergence of the new technological innovation – ‘Metaverse,’a fundamental change has been witnessed in the marketing arena with a deeper connection and inclusive experience. For marketers, the metaverse has opened up opportunities that are extremely exciting for sales and marketing. The current study is a short communication that gives a glimpse of the new marketing aspects in the metaverse that have generated fresh routes toward commerce and creativity. Design/Methodology/Approach : The current study delivered a perspective of marketing with the metaverse. Scholarly articles about this aspect were reviewed and interpreted, along with recent reports on the real business of the virtual world. Findings : The study revealed that marketers could capitalize on the metaverse, which has enlarged the breadth and depth of customer experience. Furthermore, the facets of the metaverse have provided a deeper knowledge of the preferences and behavior of customers. Practical Implications : With changing consumer behavior, the metaverse has rightly catered to the needs and demands of customers through an immersive experience. The metaverse has successfully facilitated the self-sustaining loop that has driven brand affinity for companies. Moreover, metaverse-specific marketing techniques have enhanced the strategic positioning of marketing divisions. Originality/ Value : The paper has delved deep into understanding the realistic interactions in marketing through the metaverse that are meticulously designed to stimulate customers’ emotions. The study’s insights inform about the greater personalization aspect of marketing in the metaverse that can strengthen the relationships with customers as well as the overall margins.